Reactive polymers for life sciences - Genç, Tuğba. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2010., 2010)
Synthesis of polymers with reactive side chains has attracted considerable attention since these polymers are widely utilized in bioengineering applications such as controlled drug delivery, wound dressing and tissue engineering. First part of this study introduces the synthesis of polymers decorated with succinimide and azide units as ‘reactive’ functional groups for polymer – drug conjugation. First part of this thesis expands on the polymerization, functionalization and biodegradation studies of the abovementioned polymers. Since the synthesis of such reactive polymers with narrow molecular weight distributions is desirable for many applications, Atom Transfer Radical Polymerization (ATRP) has been employed to obtain such polymers. Poly (ethylene glycol) (PEG) based polymers are known to be non-immunogenic, biocompatible and biodegradable, therefore they are promising candidates for formulation of polymer-drug conjugates. As one part of this study, water soluble PEG methacrylate based copolymers that contain amine and alkyne reactive side chains have been synthesized using ATRP. Finally, amine functionality has been proven and in vitro biodegradability behaviors depending on molecular weight, pH and composition effects were investigated. Recently, nanofibrous scaffolds are of great interest due to their unique properties and wide range of application areas. Such increased interest also necessitates synthesis of novel polymeric materials to widen the scope of intended applications of nanostructures. With this motivation, in the second part of this study, several amine, thiol or dual reactive polymers were synthesized with multifarious compositional arrangements. Electrospinning, which is a former yet still the only technique for nanofiber production, attracts attention, lately. We utilized this technique to obtain both thiol and amine reactive nanofibers and nanoparticles. The successful formation of reactive nanostructures was investigated by surface characterization techniques.
Keywords: Reactive polymers.; Polymeric drug delivery systems.